The impact of the auditor's compliance with the ethics of the auditing profession on the quality of professional performance. Theoretical research - أرشد صديق عبدالله شيخ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This research aims at the ethics of the auditing profession and the rules of professional conduct and the extent of the auditors' compliance with the ethics of the profession and what are the problems facing the auditors during their practice of the profession and what are the methods that encourage the auditors to abide by the ethics and conduct of the auditing profession. The research found several results, but the most important of which is the weakness of awareness by professional bodies about the importance of the profession and the importance of maintaining its reputation and reflection, and therefore on the society as a whole, and the lack of studies and research dealing with the aspect of professional ethics and its importance in the profession of auditor, Professional behavior and international and local auditing standards have a significant impact on decisions made by users of this information. The main recommendations in this research are to guide the auditors in the public and private sectors to abide by the rules of professional conduct and ethical standards, to observe the benefits of these rules and standards and the consequences of non-compliance with them, the need for clear and explicit codes of ethics within economic and governmental units, And to expand the preparation of studies, publications and future research on the subject of professional ethics to the importance of this subject, to overcome the imbalances experienced by the auditing profession and to raise the moral awareness among practitioners and identify the And to urge the professional organizations and bodies supervising the profession of accounting and auditing in Iraq and the Union of Accountants and Auditors and the Board of Accounting and Auditing Standards and the Board of Control to focus on the ethics of the audit profession and to adhere to them through the issuance of explanatory leaflets and the implementation of training programs and continuous learning for this purpose , And the establishment of specialized courses for this area, and to combat the drawbacks and weaknesses of the auditing profession in Iraq, and provide the necessary protection to auditors of the risks that may face them in their oversight work through Ejad mechanism that prevents employees from abuse for any reason, and to support and stimulate the material and moral independence of the auditor in all audit areas.